A Case Study on Motivation and Preferred Activities of EFL Learners in University - Elysa Hartati; Novia Ersalina Dewi; Nur Fachmi Budi Setyawan (Universitas Cokroaminoto Palopo, 2021)
This research aims to investigate the type of learners’ motivation which is predominant toward learning English as a foreign language. It is also conducted to find out the preferred activities used among English learners in a university setting. The research design was a single case study with the total sample of learners was 40 that were selected purposively from sophomore, junior and senior. The findings had shown that most of the learners were intrinsically motivated in learning English. As for learning styles, they preferred to be individually but for speaking practice, they preferred to be in small groups. It also provided evidence that the EFL learners of university preferred audio-visual activities, communicative activities, and game activities. To sum up, the English leaners have good intrinsic motivation to learn in university context, therefore, the educators especially lecturers should build the learners motivation both intrinsic and extrinsic by providing sort of discussion and individual consultation as they prefer to do in the learning activities. Thus, the lecturers and learners can get input to improve their method or strategies in teaching and learning English. At last, the success of learning English can be achieved.